2018
DOI: 10.4102/ajlm.v7i2.796
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of healthcare-associated infections in Africa: An antimicrobial resistance perspective

Abstract: BackgroundHealthcare-associated infection (HCAI) is a global health challenge, not only as an issue of patient safety but also as a major driver of antimicrobial resistance (AMR). It is a major cause of morbidity and mortality with economic consequences.ObjectiveThis review provides an update on the occurrence of HCAI, as well as the contribution of emerging AMR on healthcare delivery in Africa.MethodsWe searched PubMed, Cochrane database, African Journals Online and Google Scholar for relevant articles on HCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 46 publications
5
48
0
Order By: Relevance
“…Similar to studies done in developed [5,7,14,15] and developing countries [1,28], the most frequent pathogen in the current study was Staphylococcus aureus, a common skin colonizer. For example, it was approximately 23% in the current study compared with 20% to 30% in these studies [1,5,14,15].…”
Section: Discussionsupporting
confidence: 84%
“…Similar to studies done in developed [5,7,14,15] and developing countries [1,28], the most frequent pathogen in the current study was Staphylococcus aureus, a common skin colonizer. For example, it was approximately 23% in the current study compared with 20% to 30% in these studies [1,5,14,15].…”
Section: Discussionsupporting
confidence: 84%
“…While it is challenging to compare the distribution of SSI pathogens between different studies covering different surgical procedures, Staphylococcus aureus was the most frequent pathogen in the current study as well as studies done in developed [5,8,9] and developing countries [1,21]. For example, it was approximately 23% in the current study compared with 20 to 30% in these studies [1,5,8,9].…”
Section: Discussionmentioning
confidence: 63%
“…The current studies have reported dramatic increase of antimicrobial resistance especially in resources limited countries [5]. There is a growing body of literature that accents the significance of resistance to antibiotics that are commonly prescribed in lagging countries [6]. Therefore, there is an urgent need to address antimicrobial resistance in developing countries especially in Africa due to the fact that it is being overlooked and yet highly linked high morbidity and mortality [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent need to address antimicrobial resistance in developing countries especially in Africa due to the fact that it is being overlooked and yet highly linked high morbidity and mortality [7]. A great demand of broad-spectrum agents due to ineffectiveness of certain antibiotics on which specific pathogens have developed resistance [6,8], poses an economic burden on developing countries [7].…”
Section: Introductionmentioning
confidence: 99%